2021
DOI: 10.1111/jan.14865
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ experiences of delirium: A systematic review and meta‐summary of qualitative research

Abstract: Aims The purpose of this systematic review and meta‐summary was the aggregation of the empirical qualitative literature on patients’ experiences of delirium in order to support the development and implementation of patient‐oriented delirium management and to guide future research. Design We conducted a systematic literature review of qualitative research published between January 1980 and June 2019. Data sources In June 2019, we searched in Medline, CINAHL, SSCI and PsycInfo to identify relevant reports. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 74 publications
0
10
0
2
Order By: Relevance
“…The most common emotions were fear and anxiety. Other negative emotions reported were feeling threatened; insecurity; panic; anger; restlessness: powerlessness; helplessness; frustration; loneliness and hopelessness; vulnerability; guilt; shame; ‘going mad’; and emotional chaos [73]. Similar themes are observed in the ICU [74] and after transcatheter or surgical aortic valve replacement [75].…”
Section: Managementmentioning
confidence: 95%
See 1 more Smart Citation
“…The most common emotions were fear and anxiety. Other negative emotions reported were feeling threatened; insecurity; panic; anger; restlessness: powerlessness; helplessness; frustration; loneliness and hopelessness; vulnerability; guilt; shame; ‘going mad’; and emotional chaos [73]. Similar themes are observed in the ICU [74] and after transcatheter or surgical aortic valve replacement [75].…”
Section: Managementmentioning
confidence: 95%
“…2). A large 2011 study of non‐COVID‐19 delirium used 24 reports based on delirium experience accounts from 483 patients [73]. This included 1097 findings that were extracted and abstracted into 92 meta‐findings.…”
Section: Managementmentioning
confidence: 99%
“…This is consistent with other recent research, suggesting that delirium is often not recognized or not identified in palliative care patients (Watt et al, 2021), despite the availability of both diagnostic criteria (American Psychiatric Association, 2013) and validated delirium screening tools (Watt et al, 2021). Given that delirium is perceived as a very distressing condition by those who have experienced it and recovered (Kuusisto-Gussmann et al, 2021), it is possible that the dying patient with an altered level of consciousness is equally distressed. The findings of this integrative review agree with the previously reported findings regarding the lack of available guidance, and the difficulty in assessing the care needs of the voiceless and vulnerable dying patient with delirium (Gao et al, 2013; Lawlor et al, 2014; Blinderman and Billings, 2015; Mah et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…delirare), bemerken es zwar viele Betroffene selbst, kommunizieren dies aber nicht. Beispiele sind erste Schlaf-und Konzentrationsstörungen mit der Folge von Gedächtnislücken und Unverständnis oder verstörende Verkennungen und Halluzinationen [5]. Deshalb sind eine patienten-und familienorientierte Information und Zusammenarbeit essenziell sowie fachliche Kenntnisse aller Mitarbeiter [6].…”
Section: Einführungunclassified
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] siehe Kapitel "Erläuterungen". Wegen fehlender verlässlicher Biomarker und technischer Befunde definieren klinische Befunde das Ende der deliranten Episode.…”
unclassified